1991
DOI: 10.1111/j.1469-8749.1991.tb14961.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversational Skills of Individuals With Fragile‐x Syndrome: A Comparison With Autism and Down Syndrome

Abstract: SUMMARY The conversational skills of 18 individuals with fragile‐X syndrome (FXS) were compared with those of two other matched groups with autism and Down syndrome. The FXS group used more eliciting forms in conversation than those with Down syndrome, and also used partial self‐repetition more often than the other two groups. The Down syndrome group had more speech dysfluencies than those with autism, but not more than those with FXS. The autistic group used more inappropriate phrases. Qualitative analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 23 publications
(16 reference statements)
1
36
0
2
Order By: Relevance
“…In the Abbeduto et al [2006b] study, age-, NVMA, and NVIQ-matched participants with FXS were as likely to produce ambiguous descriptions, but more likely to include linguistic scaffolding, as were the adolescents and young adults with DS. Individuals with DS also display relatively low rates of verbal perseveration (i.e., excessive repetition) and off-topic language, each of which is a serious problem for individuals with FXS [Sudhalter et al, 1990;Ferrier et al, 1991;Belser and Sudhalter, 2001;Roberts et al, in press]. And finally, compared with same-age individuals with WS, individuals with DS are less likely to initiate conversation in inappropriate ways or used stereotyped language in conversation, although the two groups do not differ in the extent of their impairments in conversational coherence, ability to establish rapport, or use of contextual information [Laws and Bishop, 2004].…”
Section: Pragmatic Developmentmentioning
confidence: 99%
“…In the Abbeduto et al [2006b] study, age-, NVMA, and NVIQ-matched participants with FXS were as likely to produce ambiguous descriptions, but more likely to include linguistic scaffolding, as were the adolescents and young adults with DS. Individuals with DS also display relatively low rates of verbal perseveration (i.e., excessive repetition) and off-topic language, each of which is a serious problem for individuals with FXS [Sudhalter et al, 1990;Ferrier et al, 1991;Belser and Sudhalter, 2001;Roberts et al, in press]. And finally, compared with same-age individuals with WS, individuals with DS are less likely to initiate conversation in inappropriate ways or used stereotyped language in conversation, although the two groups do not differ in the extent of their impairments in conversational coherence, ability to establish rapport, or use of contextual information [Laws and Bishop, 2004].…”
Section: Pragmatic Developmentmentioning
confidence: 99%
“…Ferrier et al [1991] compared expressive language skills in a conversational context in three groups of adult males: FXS, autism, and Down syndrome. Ferrier et al found that although males with FXS used more partial self-repetition and more eliciting forms than the other two groups, they did not differ from either comparison group in expressive morphosyntax.…”
Section: Morphosyntaxmentioning
confidence: 99%
“…Males with FXS produce high rates of selfrepetition of words, phrases, and topics [Sudhalter et al, 1990;Ferrier et al, 1991;Belser and Sudhalter, 2001]. Many in the field have argued that such perseveration is a unique and defining characteristic of individuals with FXS [Bennetto and Pennington, 1996;Abbeduto and Hagerman, 1997].…”
Section: Pragmaticsmentioning
confidence: 99%
See 2 more Smart Citations